Pain Scale Reduction After a Morning Walking Program among Older Adults with Osteoarthritis: A One-Group Pretest-Posttest Study at Tlogosadang Health Center - Nadia Nasywa Candraningtyas; Dadang Kusbiantoro; Masunatul Ubudiyah (STIKep PPNI Jawa Barat, 2026)
Background: Osteoarthritis is a common degenerative joint condition in older adults and is frequently accompanied by pain, stiffness, limited mobility, and reduced quality of life. Exercise is recommended in osteoarthritis management, and walking is a low-cost activity that may be feasible in community and primary health service settings. However, evidence from small primary-care-based morning walking programs remains limited, particularly when pain medication use and the absence of a control group are considered. Objective: This study aimed to examine changes in osteoarthritis knee pain scores after a structured morning walking program among older adults in the working area of Tlogosadang Health Center, Paciran District, Lamongan Regency, Indonesia. Methods: This quantitative pre-experimental study used a one-group pretest-posttest design. The sample included 35 older adults with knee osteoarthritis selected by consecutive sampling from February to March 2026. Eligible participants were aged over 60 years, had controlled knee joint pain and limited knee movement, were able to walk, and provided informed consent. The morning walking program was delivered for 15 minutes, twice weekly for 3 weeks. Pain intensity was measured before and after the program using the Numeric Rating Scale (NRS). Data analysis treated NRS as paired ordinal pain data. The Shapiro-Wilk test was used as a distributional check, and the Wilcoxon signed-rank test was selected as the primary inferential test. Results were reported with Z statistic, p-value, and effect size r. Results: Before the program, 22 participants (62.9%) reported mild pain, 12 (34.3%) reported moderate pain, and 1 (2.9%) reported severe pain. After the program, 2 participants (5.7%) reported no pain, 28 (80.0%) reported mild pain, and 5 (14.3%) reported moderate pain. The number of respondents with moderate-to-severe pain decreased from 13 (37.2%) to 5 (14.3%). The mean NRS score decreased from 3.17 ± 1.38 to 1.86 ± 1.31, with a 1.31-point absolute reduction and an approximate 41.3% relative reduction from baseline. The Wilcoxon signed-rank test showed a statistically significant within-participant reduction (Z = -4.372, p < 0.001), with a large effect size (r = 0.74). Conclusion: Older adults with osteoarthritis showed a statistically significant reduction in pain scores after the 3-week morning walking program. Because this study had no control group and 25 participants (71.4%) reported using pain or anti-inflammatory medication, the findings should be interpreted as an observed pre-post reduction rather than definitive evidence of an independent intervention effect. Morning walking may be considered as a feasible supportive activity for older adults with osteoarthritis when safety screening and individual physical capacity are considered, but controlled studies with medication monitoring, adherence data, and adverse-event reporting are needed.